Frequency of Osteoporosis and Osteopenia According To Bone Mineral Density of Proximal Femur Subregions in Normal and Osteopenic Postmenopausal Women With Respect to Total Hip Bone - Murat Ersöz; Şenay Kahramanlar (Galenos Yayinevi, 2002)
In this study 29 normal (mean age: 65.6 ± 5.1 years) and 33 osteopenic (mean age: 67.6 ± 4.9 years) postmenopausal women according to total bone mineral density (BMD) of the hip were evaluated for BMD values of subregions of proximal femur. The percentages for osteoporosis and osteopenia with respect to subregions were 13.8% and 58.6% for femoral neck and 20.7% and 41.4% for Ward's triangle in normal group. In trochanteric and intertrochanteric measurements there were no T scores below -2.5 but 17.2% of the subjects were osteopenic with regard to trochanteric and 6.9% were osteopenic due to intertrochanteric BMD values. The percentages for osteoporosis and osteopenia with respect to subregion measurements were 57.6% and 42.4% for femoral neck, 60.6% and 36.4% for Ward's triangle, 3% and 78.8% for trochanteric, 9.1% and 87.9% for intertrochanteric regions in osteopenic group according to total hip values. Knowing that hip fracture risk is increasing 2-3 fold for 1 standart deviation decrease from the young adult mean value for all subregions and knowing the relation between cervical hip fractures and BMD values of Ward's triangle and femoral neck and the relation between intertrochanteric fractures and trochanteric BMD values, it is recommended to evaluate the BMD values of subregions of the hip besides the total hip values in daily practice.